La métropolisation parisienne : particularités et généralités - Glória da Anunciação Alves (Confins)
To speak about the metropolitan phenomenon today, in the 21st century, implies in going beyond the growing and multiplication phenomenon of the large urban agglomerations, in general continuous. The metropolization of the space is a process that today can also be characterized by the territorial discontinuity, which articulates cities from the productive processes due to the existence of (tecno-informational) nets that enable the connections among non-continuous spaces. According to Lencioni (2003) there’s a limit for that given by the area of influence and articulations with the metropolis.But to speak about the metropolization is also to go beyond the growing and multiplication of agglomeration and wealth. It’s trying to understand the contradictory process implicated in this relationship and in the places that configure the traditional metropolis, in other words, its territorial continuity.  It’s also to discuss the growing of poverty, and of the spatial differentiation. In the metropolitan expanding, with or without the public power endorsement, peripheral areas arise which are necessary for the growing of metropolitan wealth.Today the issue of the metropolitan phenomenon is institutionally put. The “Grand Plan Paris” evokes actions to promote the institutionalization of what would be the metropolization of Paris that, according to the state power is necessary to guarantee Paris in the list of the world cities, keeping it inserted in the world frame of global investments.But what does institutionalize the metropolis mean? On one side it implies in officially putting in practice a national project of international competitiveness (world scale) and on the other side, putting in focus the Paris-banlieues conflicts and relationships (local and regional scale).This article proposes to discuss the metropolization of Paris and the resulting social spatial transformations, highlighting how the speech of social mix is used justifying the social spatial segregation processes.